Modelagem do estado trófico do reservatório do Vacacaí Mirim - Kuchinski, Vinícius (2016)
The eutrophication is an environmental disorder that happens due to nutrients excess, mainly in lakes and reservoirs, from human action. This disorder causes the algal bloom, impairing the water quality, increasing the water turbidity and toxicity. This work aimed to assess the trophic state of Vacacai Mirim reservoir, located in the city of Santa Maria, southern Brazil, between 2010 and 2011, using a mathematical model for simulation and verify the water quality based on CONAMA resolution 357/2005 and on the Trophic State Index. The model used in this work is denominated CE-QUAL-W2 and was developed to water quality simulation in rivers and, principally in reservoirs. Data and information for the study area that have been published in previous work were used. These data were entered in the model as input data and then made the calibration of it. The calibration was made manually, using perturbation of parameters and has proven adequate, verifying the accuracy by the average absolute error and root mean square error. After calibration, the validation was made using a data set that was not entered as input data in calibration process. Afterwards, it was proposed extreme scenarios to verify the behavior of reservoir in front of situations of drought (30 days in length), high volume of precipitation (20x and 50x increase in rainfall volume), population growth (increase in nutrients concentration at 33, 66 and 99%) and finally, a possible treatment of effluents in the drainage basin (reduction in nutrients concentration at 33, 66 and 99%). The simulation of scenarios has shown that a drought of 30 days worsens the water quality, making the reservoir hypereutrophic and harming the classification of reservoir in reference values of Class 3 from CONAMA resolution 357/2005. The increase of precipitation dilutes nutrients and pollutants, decreasing their concentration, improving the water quality and keeping the trophic state of the reservoir. The scenario of the increase of pollutant load evidences that total phosphorous and chlorophyll-a exceeds limits reference values of Class 3, being necessary attention, because they raise the trophic state of the reservoir to hypereutrophic. The effluent discharge reduction scenario shows that, by reducing 66% the launch, there are considerable water quality gains, classifying the reservoir in Class 3 and being classified as mesotrophic.